PERTANGGUNJAWABAN PIDANA PIMPINAN KORPORASI MULTINASIONAL TERHADAP TINDAK PIDANA DUMPING LIMBAH B3 YANG DILAKUKAN OLEH PERUSAHAAN CABANG - Marthin Fransisco Manihuruk; Alvi Syahrin; Suhaidi Suhaidi; Muhammad Ekaputra (Universitas Sumatera Utara, 2018)
ABSTRACT Subsidiary establishment is a method of big scale corporations to develop their business, either in the country or cross countries. A Multinational corporation is a corporation which subsidiaries lay cross countries. This subsidiary can certainly commit a criminal act, either on purpose or due to negligence. Therefore, legal instrument is required to charge the criminal liability of the Multinational corporation.The research discusses the criminal liability of a Multinational corporation for the criminal act in B3 Dumping (Dangerous and Poisonous Waste Dumping) committed by its subsidiary. Article 60 of the Law No. 32 Year 2009 concerning the Protection and Management of Living Environment forbids everyone to do dumping to a living environment without a license. The objective of the research is to find out the criminal liability of a Multinational corporation observed from the view in which the subsidiary is the leader or the one who has given the order to commit a criminal act in B3 Dumping (Article 116 paragraph 1 of the Law No. 32 Year 2009). The complexity in this corporation problem is that it charges the liability of the Multinational corporation which subsidiary is a legal entity. It is closely related to the fact that the subsidiary is a part of the Multinational corporation, so that any charge of criminal liability cannot be addressed to only the subsidiary when it commits a criminal act. The results show that charging the criminal liability of a Multinational corporation is influenced by some aspects of the one who gives the order or the leader of the activity in committing the criminal act (Article 116 paragraph 1 of the law No. 32 Year 2009) and of the location of the corporation and it subsidiary. In addition, the aspects of nationality or citizenship of each head of corporation and it subsidiary is limited by article 2-9 of KUHP (the Criminal Code) stating that the limitations of the effectiveness of criminal laws will influence one to another. Keywords: Criminal Liability of a Multinational Corporation, Dumping, Subsidiary